2007
DOI: 10.1145/1272848.1272879
|View full text |Cite
|
Sign up to set email alerts
|

Failure rates in introductory programming

Abstract: It is a common conception that CS1 is a very difficult course and that failure rates are high. However, until now there has only been anecdotal evidence for this claim. This article reports on a survey among institutions around the world on failure rates in introductory programming courses. The article describes the design of the survey and the results. The number of institutions answering the call for data was unfortunately rather low, so it is difficult to make firm conclusions. It is our hope that this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
212
1
30

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(255 citation statements)
references
References 7 publications
12
212
1
30
Order By: Relevance
“…Uma pesquisa realizada por Bennedsen e Caspersen [2007], com a participação de 63 instituições de diversos países, obtiveram um índice de 67% de aprovações, ou seja, 33% de reprovações, trancamentos e desistência caracterizando insucesso na tentativa de aprender a programar.…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation
“…Uma pesquisa realizada por Bennedsen e Caspersen [2007], com a participação de 63 instituições de diversos países, obtiveram um índice de 67% de aprovações, ou seja, 33% de reprovações, trancamentos e desistência caracterizando insucesso na tentativa de aprender a programar.…”
Section: Revisão Da Literaturaunclassified
“…trancamentos na disciplina e até desistência do curso. Bennedsen e Caspersen [2007] afirmam que cursos de computação são difíceis e apresentam alta taxa de insucesso. Poucas pesquisas mostram dados quantitativos do índice de reprovações e linguagens de programação utilizadas.…”
Section: Introductionunclassified
“…A more recent study [2] also found that the student success rates in introductory programming classes are very low.…”
Section: Introductionmentioning
confidence: 98%
“…It has even been mentioned that one out of three students fails the class at entry level programming courses in universities (Bennedsen & Caspersen, 2007) and that programming is one of the most difficult subjects in the undergraduate curriculum (Jenkins, 2002). Meisalo and colleagues also reported that 32% of college learners have dropped out their programming courses, which were offered as distance education and when asked for their reasons, students all pointed out that the subject was simply too difficult (Meisalo, Suhonen, Torvinen, & Sutinen, 2002).…”
Section: Introductionmentioning
confidence: 99%